Evaluation of compatibility of the generic competencies defined for Latin-American Tuning project (2011-2013): a case study (2011-2013) - Zapata Chapman, Rodrigo (Educare (Caracas), 2021)
The higher education institutions decided to work on the creation of a general competencies framework that allows their graduates to meet the requirements of the global labor market, adapting to the Tuning project created in Europe and adapted in Latin America. Being it an independent project that aims to establish reference points, convergences, and mutual understanding,  according to certain generic and specific competencies. This research seeks to determine if the foreign trade and international business programs of the Escolme University Institution have developed the competencies established in the Latin-America Tuning Project proposal. The methodology applied is based on a quantitative approach through a case study in which all the students of these programs participated. Among the results, there is a low development of competencies allowing us to conclude that both the participants of technology in foreign trade and those of professionalization of international businesses do not comply with the generic competencies defined by the Tuning Latin America Project.